Asian Infrastructure Investment Bank (AIIB)'s sustainable safeguard mechanism on energy projects. (November 2021) - Shao, Mengqi; Tan-Mullins, May; Xie, Linjun
Abstract: Asian Infrastructure Investment Bank (AIIB) was officially established by China in 2016 with one of the aims to develop energy infrastructure based on green and sustainable principles in Asia. To achieve that, AIIB has set forth safeguard policies, including the Environmental and Social Framework (ESF) applied for funded projects and the AIIB Energy Sector Strategy, to guide its energy investments. However, the effects of the safeguard policies and further safeguard operations on the energy projects remain unknown. This study reviews AIIB's safeguard mechanism on energy projects, including the safeguard policies, assessment and management plans, and implementations of AIIB's energy projects. We find that AIIB's current safeguard mechanism on energy projects, in comparison with other established multilateral development banks (MDBs), is still at its beginning stage, which does not match its goal and promise on sustainable energy development in Asia. Highlights: This paper examines AIIB's safeguard mechanism, including its safeguard policies and safeguard operations. This paper finds the gaps of AIIB's safeguard policies by comparing that to the practices of other established MDBs. This paper identifies the gaps of AIIB's safeguard operations by comparing co-financed and stand-alone energy projects.